2013
DOI: 10.1039/c3ta13250a
|View full text |Cite
|
Sign up to set email alerts
|

A new class of thermo-switchable hydrogel: application to the host–guest approach

Abstract: The successful construction of a thermogelling system for the hydrophobically modified polyacrylamide (HMPAM)/a-CD mixture is reported featuring an application to the host-guest approach. It has been shown that the thermogelling property, masked by the strong intermolecular hydrophobic interaction, can be engineered to display by means of the host-guest approach, requiring no special synthesis, no third competitive guest and no harsh conditions. The findings of this work provide the basis for understanding and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The thermal hysteresis phenomenon ( T C < T m ) was observed in the representative hydrogel. It was a common phenomenon for thermal‐sensitive polymer systems according to previous studies, reflecting the gelation was an entropy‐driven process. Meanwhile, the elastic modulus G ′ correlated excellently with the results obtained from DSC curves.…”
Section: Resultsmentioning
confidence: 86%
“…The thermal hysteresis phenomenon ( T C < T m ) was observed in the representative hydrogel. It was a common phenomenon for thermal‐sensitive polymer systems according to previous studies, reflecting the gelation was an entropy‐driven process. Meanwhile, the elastic modulus G ′ correlated excellently with the results obtained from DSC curves.…”
Section: Resultsmentioning
confidence: 86%
“…When the strain increased over 80%, the G 0 and G 00 values decreased sharply, indicating the dislocation and cut-off of polymer chains 18 or physical cross-linking points. 24 Further, the G 00 are higher than G 0 values when strain increased to 300-400%, representing a gel-sol transition.…”
Section: Resultsmentioning
confidence: 93%
“…It is already well known that the host‐guest approach between α‐CD and the hydrophobic units of polymer chains is versatile and can be used effectively to prepare a variety of high‐performance materials. We have already shown that a novel thermo‐responsive self‐healing hydrogel can be developed by introducing the host‐guest approach between α‐CDs and hydrophobic units (C12) of polymer chains, requiring no special synthesis, no third competitive guest or harsh conditions . In this study, we found with astonishment that a novel thermo‐responsive shape memory hydrogel could also be developed by introducing the host‐guest approach between α‐CDs and the hydrophobic units of polymer chains.…”
Section: Introductionmentioning
confidence: 82%